An observational comparative study of intraocular pressure changes in post-operative cataract patients treated with dexamethasone and difluprednate - Hingorani, Sadhana K.; Desai, Anupama S.; Shastri, Manisha B. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Cataract is the leading cause of blindness worldwide. Treatment of cataract is surgical. Topical corticosteroids are routinely used in the treatment of post-operative inflammation following cataract surgery. This study aims to compare the intraocular pressure changes caused by topical steroids (dexamethasone and difluprednate) and to detect adverse effects. Methods: All patients operated by phacoemulsification in ophthalmology Department of SMIMER Surat were taken as subjects. Depending on topical steroids prescribed after surgery, subjects were separated into 2 groups, group 1 - difluprednate and group 2 - dexamethasone. Changes in intra-ocular pressure (IOP) of patients were collected from the data available pre-operative, 1st ,2nd ,3rd ,4th week after surgery and were analyzed. Other parameters whose data were collected are-adverse effects and compliance of patients. Results: In group 1 preoperative mean IOP was 15.5. At the end of 1st week, the mean IOP was significantly increased to 15.8. There was equal rise in IOP during 3rd week and 4th week which means that after 3rd week IOP remains stable. In group 2 preoperative mean IOP was 15.4. At the end of 1st, 2nd, 3rd and 4th there was significant increase in IOP as compared to preoperative mean IOP. Adverse effects were reported more in group 2. Conclusions: In group 1 there was a rise in IOP up to three weeks but after 3rd week IOP remained stable. In group 2 rise in IOP was seen throughout 4 weeks of treatment. Adverse effects seen more in group 2. Compliance of patients was better in group 1.